Acute caffeine and capsaicin supplementation and performance in resistance training - Carolina B. Simões; Paula Louise C. Gomes; Ronaldo A.D. Silva; Igor C.S. Fonseca; Mariana Fonseca; Vernon M. Cruz; Marcos D.M. Drummond (Universidade Estadual Paulista (UNESP), 2021)
Abstract Aim: This study aimed to evaluate the acute supplementation effects of capsaicin, caffeine, and the combined capsaicin plus caffeine on total volume (total repetitions x weight lifted), rate of perceived exertion (RPE), and side-effects on resistance training. Methods: Eleven men (21.5 ± 2.1 years, 1.75 ± 0.08 m, 79.64 ± 10.1 kg), trained in resistance training (experience of 4.5 ± 2.6 years, weekly frequency 5 ± 0.8 days) were recruited. This was a crossover, randomized, double-blind study. Each volunteer went through four experimental conditions: supplemented with capsaicin (12 mg), caffeine (400 mg), capsaicin plus caffeine (12 mg and 400 mg, respectively), or placebo. After supplementation, the volunteers completed four sets of back squats until failure, at 70% of one-repetition maximum, with 90 s of rest interval between sets. RPE was registered at the end of each set. Volunteers were asked about the occurrence of side effects, right after exercise and 24 h after supplementation. Results: No significant differences were found (p > 0.05) in total volume between placebo (5505.2 ± 810.7 kg), capsaicin (6010.0 ± 1067.0 kg), capsaicin plus caffeine (5885.1 ± 1219.3 kg), and Caffeine (5628.6 ± 894.4 kg). No significant differences were found in RPE (p > 0.05) between the experimental conditions. The effect size of the total volume was small in capsaicin and capsaicin plus caffeine (d = 0.62 e d = 0.47, respectively), and trivial in the caffeine condition (d = 0.15). Conclusion: The supplementation failed to influence resistance training performance as well as had no effects on increasing the total volume or reducing RPE.